Answer: I think the answer is 38.
Step-by-step explanation:
very simple it's b. tell me if you need help with anything els
A. (3x7)+(3x4)
should be the correct one bc the other options dont get the same answer in the end
The radical equation is
![\sqrt{x+6}-5=x+1](https://tex.z-dn.net/?f=%20%5Csqrt%7Bx%2B6%7D-5%3Dx%2B1%20)
.
i) We first isolate the square root, adding 5 to both sides of the equation:
![\sqrt{x+6}=x+6.](https://tex.z-dn.net/?f=%20%5Csqrt%7Bx%2B6%7D%3Dx%2B6.%20)
ii) Here let's substitute x+6 with t. Doing so we have:
![\sqrt{t}=t.](https://tex.z-dn.net/?f=%20%5Csqrt%7Bt%7D%3Dt.%20)
Squaring both sides, we get:
![t=t^2](https://tex.z-dn.net/?f=t%3Dt%5E2)
iii) Collecting the variables on the same side, and factorizing t we have:
![t(t-1)=0](https://tex.z-dn.net/?f=t%28t-1%29%3D0)
, which yields
t=0 or t=1.
Now we solve for x in x+6=t:
x+6=0 ⇒x=-6 and x+6=1⇒x=-5.
iv) Now we check these values in the original equation
![\sqrt{x+6}=x+6](https://tex.z-dn.net/?f=%20%5Csqrt%7Bx%2B6%7D%3Dx%2B6)
:
a)
![\sqrt{-6+6}=-6+6.](https://tex.z-dn.net/?f=%20%5Csqrt%7B-6%2B6%7D%3D-6%2B6.%20)
⇒ 0=0 ; Correct.
b)
![\sqrt{-5+6}=-5+6.](https://tex.z-dn.net/?f=%20%5Csqrt%7B-5%2B6%7D%3D-5%2B6.%20)
⇒ 1=1 ; Correct.
Answer: <span>x = −6 and x = −5 </span>